(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
There have been found out classification basis of studying valence category in modern linguistics; there have been grounded the qualification principles of formal and syntactical valence; there have been described its grammar structure within functional perspective of means of explication and defined differential features of two kinds of formal and syntactical valence – non-derivative and derivative.